Re-Assessing the Impacts of Exports on Local Labour Market Outcomes: A Supply Chain Perspective. Evidence from Egypt - Pablo Tillian; Deeksha Kokas; Carlos Góes; Gladys Lopez-Acevedo (Institute of Labor Economics (IZA), 2023)
This paper examines the overall impact of exports while accounting for supply chain linkages on local labor market outcomes in Egypt between 2007 and 2018. We assess the effects not only on directly exporting industries but also on industries indirectly affected by rising export demand. Furthermore, we examine potential impacts on specific worker groups, such as high-skilled individuals and female workers. The results show that trade does not lead to the same connection with domestic labor markets in Egypt as observed in other countries, as highlighted in the existing literature explaining the adverse effects of imports on developing countries. Despite being more open to trade, trade-intensive industries in Egypt have not experienced a significant increase in their share of employment within the overall workforce.
Keywords: F13; F14; F15; F16; J23; J31; O15; O19; 330; trade policy; trade flows; labor market outcomes; firm dynamics